Notes on market design and economic sociology - José Ossandón (economic sociology_the european electronic newsletter, 2019)
Consider the following two examples: Inspired by Milton Friedman's proposal that demand-side subsidies and consumer choice would enhance school competition, which in turn should improve learning and the efficiency of the system as a whole, policymakers radically reformed school education in Chile in the early 1980s. After several regulatory modifications, education in Chile is still heavily market- based. However, since the massive student revolt of 2011, the area has been hugely controversial. One of the main issues has been that, in the current system, not only are parents trying to choose the best schools for their children, schools, in order to maintain or improve their positions in the national test that ranks them, are actively excluding students with learning difficulties or families that seem to them to be more complicated. In order to find a way out of the impasse, policymakers are currently implementing a particular technical solution, namely centralized clearing-house mechanisms, such as the one implemented in Boston and developed by economists such as Alvin E. Roth. The work of market designers, Roth explains, "is to know the workings and requirements of particular markets well enough to fix them when they're broken or to build markets from scratch when they're missing" (Roth 2007: 1). Policymakers in Chile intend to re-design the existing school education market in order to reduce discrimination...
Keywords: 330